How Screendance Was Invented While We Were Busy Claiming It Wasn’t - Vaghi, Katja (The International Journal of Screendance, 2019)
Many screendance authors seem to worry about the marginalized state of the practice and its lack of a solid scholarly discourse. This leitmotif goes against my perception of screendance as one of the fastest growing fields in dance, both in practice and theory. This short provocation considers some reasons for this feeling of lack and, by juxtaposing them with reflections on the advent of new institutionalized courses in screendance, invites us to revise our perception of the field. Screendance has finally reached a critical mass of works and research to ‘stand by itself.’